Investigation on production of bleachable chemi-mechanical pulp from wheat straw - Ahmad Jahan latibari (Regional Information Center for Science and Technology (RICeST), 2011)
In an attempt to develop pulping process suitable for small scale implementation, production of bleachable chemi-mechanical pulp from wheat starw is investigated. Four levels (10, 12, 14 and 16% based on oven dry weight of straw) NaOH and three pulping times (20, 30 and 40 minutes) at 95°C pulping temperature were used. After digester yield varied between 64.65 and 71.7% and the total yield after defibration was measured as 54.45% and 62%.  Unrefined pulp freeness varied between 708 and 765 ml CSF. Pulps produced applying 10-16% NaOH, 40 minutes pulping time and 95°C pulping temperature was selected from further evaluation. These pulps were refined to about 365 ml CSF in a PFI mill and then handsheets were made for strength evaluation. The apparent density of the handsheets varied between 437-488 kg/m3, tear index between 6.51-7.11 mN.m2/g, and tensile index between 29.2 -30.8 N.m/g. Significant difference at 99%  was not observed between the strength of the pulps. Then pulp produced applying 10% NaOH, 40 minutes pulping time and 95°C pulping temperature was selected for bleaching trials. Totally Chlorine Free (TCF) bleaching sequence was used for bleaching the selected pulp.  Pulps bleached applying 4% H2O2 and 3.5% NaOH, 3% sodium Silicate, 0.5% MgSO4 and 0.3% DTPA for 2 hours showed the highest brightness of 50.69% compared to 29.2% for unbleached pulp.